Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies (Open Book Publishers, 2024)
Meta-Xenakis offers readers a comprehensive collection of insights into the history, works and legacy of Iannis Xenakis, one of the twentieth century’s most significant creative figures. It presents a transcontinental engagement with his life and output, focusing as much on the impact of the questions he posed as on the accomplishments of his body of work. This volume evolved out of the multi-modal, international Meta-Xenakis Consortium’s artistic and scholarly events commemorating his centenary. Informative and comprehensive, contributions span subjects including music composition, creative pedagogy, aesthetics, game theory, architecture, and the social and political contexts in which Xenakis operated. The book is organized in eight sections, centered on different facets of Xenakis’s work and reception. It includes a digital archive of audio and visual media from the events staged throughout 2022, as well as computer software. Bringing into conversation the diverse perspectives and insights of researchers, musicians and artists, this volume serves as a foundational resource for future research on the life and work of Xenakis. It will be of interest to students, scholars, and practitioners across a range of disciplines including music, architecture, cybernetics and computation, and the digital arts.